2021
DOI: 10.3390/jcm10235490
|View full text |Cite
|
Sign up to set email alerts
|

Vessel Density in the Macular and Peripapillary Areas in Preperimetric Glaucoma to Various Stages of Primary Open-Angle Glaucoma in Taiwan

Abstract: Peripapillary and macular vessel density (VD) are reduced in myopic non-glaucomatous eyes, the dynamic range of VD may be decreased by myopia, and whether VD measurement has the potential in differentiating stages of glaucoma severity in patients with myopic glaucoma remains questionable. This observational, cross-sectional study aimed to clarify the changes in peripapillary and macular VDs in preperimetric glaucoma (PPG) and primary open-angle glaucoma in the early, moderate, and late stages. A total of 1228 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…26 In addition, reduced ONH VD has been observed in patients with glaucoma, diabetes mellitus, and subcortical vascular cognitive impairment. [27][28][29] There is limited research into changes in macular VD following COVID-19. 20,30,31 Some studies have reported ONH changes after COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 In addition, reduced ONH VD has been observed in patients with glaucoma, diabetes mellitus, and subcortical vascular cognitive impairment. [27][28][29] There is limited research into changes in macular VD following COVID-19. 20,30,31 Some studies have reported ONH changes after COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“… 26 In addition, reduced ONH VD has been observed in patients with glaucoma, diabetes mellitus, and subcortical vascular cognitive impairment. 27 29 …”
Section: Discussionmentioning
confidence: 99%
“…The mean defect of visual field more than -2 dB would be considered as abnormal visual field. Our study team have built up a normal ground of OCT and OCTA for normal subjects with different axial length [ 18 ]. All glaucoma patients were followed more than 1 years and their collected data was confirmed by an experienced glaucoma specialist.…”
Section: Methodsmentioning
confidence: 99%
“…Changes leading to a reduced density and calibre of retinal blood vessels occur during glaucoma [1,[6][7][8]. Numerous studies using optical coherence tomography angiography (OCTA) have shown significant reductions in the flow density, flow index, and vessel density in the optic nerve head and macula in patients with glaucoma compared to controls, as well as the association between these parameters and changes in the visual field [6,[9][10][11][12]. Colour Doppler Imaging has demonstrated reduced velocities and an increased resistivity index in intraocular vessels in glaucoma patients [13].…”
Section: Introductionmentioning
confidence: 99%